KNOWLEDGE CONSTRUCTION OF CAESAREAN SECTION AMONG WOMEN IN NORTHERN GHANA - Amike, J.; Yidana, A. (UDS International Journal of Development, 2023)
The study sought to determine the prevalence of cesarean section among women who delivered at the Tamale Teaching Hospital. Cesarean section is performed when a vaginal delivery is risky to the baby and mother. Even though the benefits of Caesarean section are known to women, many would often opt for vaginal delivery to boost their social recognition as women. The design was a hospital-based descriptive cross-sectional study among women within the Tamale Metropolis. The study employed a qualitative method. There were four focus group discussions to elicit information from women who experienced Caesarean Section. Many participants had good knowledge about the risk and effects of a Caesarean Section. Respondents with cesarean section experience did not have a choice to decline in the study hospital because all were emergency cases. Friends and relatives influenced the belief of respondents about cesarean section. Some of the reasons assigned for not opting for a cesarean section were; fear of complications, uncertainty regarding the pain during and after the procedure, and the fact that it is not a natural phenomenon. The perception of society regarding womanhood strongly emerged as an order of socialization and revealed that women who experienced Caesarean section go through ridicule in their respective communities. There is a growing trend of misconception about cesarean section. The Ministry of Health in Ghana should ensure that all health personnel, especially nurses and midwives, have location-based training on sociocultural beliefs about Caesarean section. Keywords: Women, Knowledge, Experience, Social Construction, Caesarean Section